Interconnection between several eye biomechanical and biometric parameters in children with axial and refractive mild myopia - T. Ye. Tsybulskaya (Zaporožskij Medicinskij Žurnal)
Aim – to study the relationship of biometric and biomechanical indicators of corneoscleral capsule of the eye in children with axial and refractive mild myopia.